Kompetensi Sosial Guru dalam Mengembangkan Pembelajaran IPS di Madrasah - Setiawan, Edi; Ningsih, Tutuk (ARZUSIN, 2025)
This research aims to analyze the social competence of teachers in developing Social Studies (IPS) learning at Madrasah Ibtidaiyah Ma’arif NU 01 Karangkemiri. The social competence of teachers is an important factor in creating effective interactions with students, colleagues, and parents, thereby contributing to the improvement of student learning motivation and engagement in the learning process. This research uses a qualitative approach with a case study method. The population in this study consists of all social studies teachers at the madrasa, with a sample of one fourth-grade teacher selected purposively. Data were collected through observation, interviews, and documentation. Data analysis was conducted in three main stages: data reduction, data presentation, and conclusion drawing. The research results show that teachers have good social competence in managing classroom interactions, applying effective communication strategies, and building harmonious relationships with students' parents. Learning methods such as group discussions and project-based approaches have proven to enhance student participation and understanding of social studies material.